Improved robustness of ex-situ biological methanation for electro-fuel production through the addition of graphene. (December 2021) - Wu, Benteng; Lin, Richen; Kang, Xihui; Deng, Chen; Dobson, Alan D.W.; Murphy, Jerry D.
Abstract: Ex-situ biomethanation (CO2  + 4H2 → CH4  + 2H2 O) can simultaneously achieve renewable electricity storage and CO2 valorisation. However, fluctuations in variable renewable electricity may lead to intermittent hydrogen supply, which is shown to adversely affect microbial activity and performance of the biomethanation process. Carbonaceous materials may act as an abiotic additive to enhance microbial robustness and improve system performance. Nanomaterial graphene and pyrochar were compared to assess their effects on biomethanation systems with an intermittent supply of hydrogen. Results revealed that intermittent gas supply caused deterioration in the restart performance with only 66% of theoretical methane production obtained in the control compared with 84% under steady state conditions. The addition of graphene in biomethanation led to 78% of the theoretical methane production after repetitive intermittent supply; this improvement is postulated to be due to its high electrical conductivity and large specific surface (500 m 2 /g). In comparison, pyrochar amendment did not lead to a significant improvement in upgrading performance. Microbial analysis showed that the OTUs affiliated to bacteria withinin the order SHA-98 (42.9% in abundance) and archaea from the genus Methanothermobacter (99%) may result in the establishment of a new syntrophic relationship to improve the robustness of biomethanation process. Graphical abstract: Image 1 Highlights: Graphene and pyrochar were assessed in an intermittent biomethanation system. Intermittent gas supply decreased the gas conversion efficiency by 21.6%. Graphene recovered 78% of gas conversion efficiency after intermittent gas supply. Pyrochar addition induced short-period inhibitory effects on upgrading performance. Microbes affiliated with SHA-98 and Methanothermobacter may play a critical role.